AB1171 COMPUTER-BASED EVALUATION OF JOINT SPACE NARROWING IN PATIENTS WITH RHEUMATOID ARTHRITIS TREATED WITH WITH CERTOLIZUMAB PEGOL. (June 2019) - Pfeil, Alexander; Nussbaum, Anica; Renz, Diane; Malich, Ansgar; Böttcher, Joachim; Wolf, Gunter; Oelzner, Peter
Abstract : Background: The reduction of finger joint space width in patients with rheumatoid arthritis (RA) is associated with joint destruction. Anti-TNF treatment with certolizumab pegol is an effective therapy in RA-patients. The computer-assisted joint space analysis is a new computer based technique to measure joint space width on hand radiographs. Objectives: The aim of this post-hoc analysis of the data set used in the RAPID 1 trial was to quantify finger joint space width of RA patients treated with Certolizumab pegol. Methods: The post-hoc analysis includes 328 patients. These patients were divided into three groups: methotrexate plus placebo, certolizumab pegol 200 mg (every two weeks) plus methotrexate, and certolizumab pegol 400 mg (every two weeks) plus methotrexate. All patients underwent x-rays of the hand at baseline and week 52 as well as the quantification of finger joint space width of the metacarpal-phalangeal articulations (MCP) using the computer-assisted joint space analysis (Version 1.3.6; Sectra; Sweden). The joint space distance is expressed as mean joint space width of the MCP joints I to V (JSD-MCP total). Results: The methotrexate group presented a significant joint space reduction with -4.8% for JSD-MCP total from 0.151 ± 0.028 cm (baseline) to 0.144 ± 0.033 cm (week 52). For the patients treated with certolizumab pegol 400 mg a non-significant change (0.6%) of JSD-MCP total from 0.146 ± 0.034 cm (baseline) to 0.147 ± 0.036 cm (week 52) was observed. A similar result was evaluated for the certolizumab pegol 200 mg group (JSD-MCP total: 0.147 ± 0.035 cm [baseline] to 0.147 ± 0.036 cm [week 52]). Conclusion: The study highlights that patients treated with certolizumab pegol plus methotrexat show no change of joint space width of the metacarpal-phalangeal articulations in comparison to patients with methotrexate plus placebo estimated by computer-assisted joint space analysis. Consequently, the automatic quantification of finger joint space is a sensitive technique for the quantification of joint space reduction and treatment monitoring. References: [1] Keystone E, Heijde Dv, Mason D Jr, et al. Certolizumab pegol plus methotrexate is significantly more effective than placebo plus methotrexate in active rheumatoid arthritis: findings of a fifty-two-week, phase III, multicenter, randomized, double-blind, placebo-controlled, parallel-group study. Arthritis Rheum 2008;58:3319-29. Disclosure of Interests: Alexander Pfeil Grant/research support from: This study is a part of the Investigator Initiated Study "The quantification of inflammatory related periarticular bone loss in certolizumab pegol treated patients with rheumatoid arthritis" which is funded and supported by UCB Pharma GmbH, Monheim, Germany (number: IIS-2014-101458)., Anica Nussbaum: None declared, Diane Renz: None declared, Ansgar Malich: None declared, Joachim Böttcher: None declared, Gunter Wolf: None declared, Peter Oelzner: None declared